Frontispiece: Recent Advances in the Chemistry of Heavier Group 14 Enolates. Issue 67 (2nd December 2019) - Haas, Michael
Abstract : Recently, heavier Group 14 enolates have shown their importance and applicability in a broad range of chemical transformations. They are key intermediates during the synthesis of photoinitiators, as well as during the formation of complex silicon frameworks. For more information on strategies towards their synthesis, together with structural properties and spectroscopic behavior, see the Minireview by Michael Haas on page 15218 ff.